Relationship of prediagnostic body mass index with survival after colorectal cancer: Stage‐specific associations. Issue 5 (14th May 2016) - Kocarnik, Jonathan M.; Chan, Andrew T.; Slattery, Martha L.; Potter, John D.; Meyerhardt, Jeffrey; Phipps, Amanda; Nan, Hongmei; Harrison, Tabitha; Rohan, Thomas E.; Qi, Lihong; Hou, Lifang; Caan, Bette; et al.
Abstract : Higher body mass index (BMI) is a well‐established risk factor for colorectal cancer (CRC), but is inconsistently associated with CRC survival. In 6 prospective studies participating in the Genetics and Epidemiology of Colorectal Cancer Consortium (GECCO), 2, 249 non‐Hispanic white CRC cases were followed for a median 4.5 years after diagnosis, during which 777 died, 554 from CRC‐related causes. Associations between prediagnosis BMI and survival (overall and CRC‐specific) were evaluated using Cox regression models adjusted for age at diagnosis, sex, study and smoking status (current/former/never). The association between BMI category and CRC survival varied by cancer stage at diagnosis (I‐IV) for both all‐cause ( p‐ interaction = 0.03) and CRC‐specific mortality ( p‐ interaction = 0.04). Compared to normal BMI (18.5–24.9 kg/m 2 ), overweight (BMI 25.0–29.9) was associated with increased mortality among those with Stage I disease, and decreased mortality among those with Stages II–IV disease. Similarly, obesity (BMI ≥30) was associated with increased mortality among those with Stages I–II disease, and decreased mortality among those with Stages III–IV disease. These results suggest the relationship between BMI and survival after CRC diagnosis differs by stage at diagnosis, and may emphasize the importance of adequate metabolic reserves for colorectal cancer survival in patients with late‐stage disease. Abstract : What's new? Being overweight increases a person's risk of developing colorectal cancer, but does it also influence the likelihood of surviving it? These authors investigated. Drawing on data from six prospective cohort studies, they analyzed the relationship between body mass index before diagnosis and odds of survival. Because survival depends greatly on how advanced the cancer is when it's discovered, they controlled for stage at diagnosis. Interestingly, the effect of weight differed depending on disease stage. Among those with Stage I disease, being overweight appeared to increase mortality, but for those with Stage II–IV disease, higher BMI meant better survival.